HPMA-based polymeric micelles for curcumin solubilization and inhibition of cancer cell growth - Naksuriya, Ornchuma; Shi, Yang; van Nostrum, Cornelus F.; Anuchapreeda, Songyot; Hennink, Wim E.; Okonogi, Siriporn (European journal of pharmaceutics and biopharmaceutics, 2015)
[Display omitted] Curcumin (CM) has been reported as a potential anticancer agent. However, its pharmaceutical applications as therapeutic agent are hampered because of its poor aqueous solubility. The present study explores the advantages of polymeric micelles composed of block copolymers of methoxypoly(ethylene glycol) (mPEG) and N-(2-hydroxypropyl) methacrylamide (HPMA) modified with monolactate, dilactate and benzoyl side groups to enhance CM solubility and inhibitory activity against cancer cells. Amphiphilic block copolymers, ω-methoxypoly(ethylene glycol)-b-(N-(2-benzoyloxypropyl) methacrylamide) (PEG-HPMA-Bz) were synthesized and characterized by 1H NMR and GPC. One polymer with a molecular weight of 28,000Da was used to formulate CM and compared with other aromatic substituted polymers. CM was loaded by a fast heating method (PEG-HPMA-DL and PEG-HPMA-Bz-L) and a nanoprecipitation method (PEG-HPMA-Bz). Physicochemical characteristics and cytotoxicity/cytocompatibility of the CM loaded polymeric micelles were evaluated. It was found that HPMA-based polymeric micelles significantly enhanced the solubility of CM. The PEG-HPMA-Bz micelles showed the best solubilization properties. CM loaded polymeric micelles showed sustained release of the loading CM for more than 20days. All of CM loaded polymeric micelles formulations showed a significantly potent cytotoxic effect against three cancer cell lines. HPMA-based polymeric micelles are therefore promising nanodelivery systems of CM for cancer therapy.